Lock ‘Em Up and Set Them Free?: How to Reconcile Tough-on-Crime Sentencing Policies with Justice Reinvestment in Maryland - Daniel G. Solomon (Washington University Journal of Law & Policy, 2019)
This note examines two pieces of contemporaneously enacted criminal justice legislation in Maryland: one law reflecting a tough-on-crime approach, and another aimed at reducing over-incarceration. The note addresses various policy arguments in favor of and against each piece of legislation, against the backdrop of relatively high rates of crime in Baltimore. The note ultimately endorses the legislation that increased incarceration periods for certain offenses, but argues that this legislation should be paired with even more robust legislation to combat over-incarceration than Maryland currently has.
Keywords: criminal justice; legislation; Maryland; Baltimore; tough-on-crime; mass incarceration